PERLINDUNGAN HUKUM PESERTA JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT UMUM DAERAH BANYUMAS - Dwinanda Pangestika Hariastuti (MIH Unsoed, 2017)
Implementation of the programmed government's health is a national health insurance is BPJS. BPJS Health seeks to provide legal protection to participants Not PBI especially in health facilities in hospitals Banyumas. The method used is specific normative juridical with descriptive analytical, secondary data sources, approach to law and analytical approach. The study was conducted at Hospital Banyumas and PII UNSOED. Therefore concluded legal protection of participants Not PBI not inpatient national health insurance in hospitals Banyumas form of preventive rights, the right to curative, rehabilitative rights both administratively and medically. The legal protection of participants Not PBI not inpatient national health insurance in hospitals Banyumas a right of preventive, rights curative, right rehabilitative both administratively and medically well as the right form of accommodation in the form of class hospitalization non intensive consisting of classrooms III, classroom II, I classrooms and intensive inpatient treatment.Keywords: Hospital Banyumas. Legal Protection, National Health Insurance